Liquid dairy waste as fertilizer for ‘Mombaça’ grass - Santos, Perlon Maia; Silva, José Expedito Cavalcante; Santos, Antonio Clementino; Santos, Jose Geraldo Donozetti; Araújo, Aridouglas Santos; Rodrigues, Marcos Odilon Dias (Federal University of Piauí, 2016)
The chemical or organic fertilizer can be responsible for the sustainability of pastures, with an alternative of application for the agro-industry subproducts. This study aimed to evaluate the influence of dairy waste application on Mombaça grass agronomic characteristics to verify the potential supply of phosphorus (P) and potassium (K). Six doses of liquid dairy waste corresponding to 10, 50, 100, 150, 200 and 400 m³ ha-¹ were evaluated in four production cycles. The accumulation of dry forage, leaf blade, stem, dead material, leaf area index, number of tillers, leaf/stem and plant height were evaluated. Increasing levels resulted in the increase of the grass performance. The application of 400 m³ ha-¹ of liquid dairy waste ensures similar productions when compared to the application of P and K through chemical fertilizers, replacing 25% of the phosphorus and 100% of potassium fertilization. The liquid dairy waste can be used as a potassium supplier to Mombaça grass and have a positive residual effect on biomass accumulation.